2005
DOI: 10.1007/s00210-005-1051-9
|View full text |Cite
|
Sign up to set email alerts
|

Unique excitation–contraction characteristics of mouse myocardium as revealed by SEA0400, a specific inhibitor of Na+–Ca2+ exchanger

Abstract: The functional role of the sodium-calcium exchanger in mouse ventricular myocardium was evaluated with a newly developed specific inhibitor, SEA0400. Contractile force and action potential configuration were measured in isolated ventricular tissue preparations, and cell shortening and Ca2+ transients were measured in indo-1-loaded isolated ventricular cardiomyocytes. SEA0400 increased the contractile force, cell shortening and Ca2+ transient amplitude, and shortened the late plateau phase of the action potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 22 publications
3
35
2
Order By: Relevance
“…However, in the range of physiological heart rates (200-600 bpm, or 3.3-10 Hz), the contraction amplitude showed no detectable frequency dependence. This observation conforms with the other reports that showed the negative force-frequency relationship of mouse heart muscle, which developed only at stimulation frequencies lower than 1-2 Hz [22,23].…”
Section: Properties Of the Isolated Heart Cellssupporting
confidence: 93%
See 1 more Smart Citation
“…However, in the range of physiological heart rates (200-600 bpm, or 3.3-10 Hz), the contraction amplitude showed no detectable frequency dependence. This observation conforms with the other reports that showed the negative force-frequency relationship of mouse heart muscle, which developed only at stimulation frequencies lower than 1-2 Hz [22,23].…”
Section: Properties Of the Isolated Heart Cellssupporting
confidence: 93%
“…4A. The contraction had an amplitude of 8.2 ± 2.2% (n = 8) of the resting cell length at a stimulation frequency of 300 bpm, and was larger at lower stimulation frequency (16.5 ± 1.6% at 60 bpm), being consistent with the negative force-frequency relation known for the heart muscle of the mouse [17,19,22,23]. However, in the range of physiological heart rates (200-600 bpm), the contraction amplitude showed no significant frequency-dependence (p = 0.47 by one-way ANOVA).…”
Section: Contraction Properties Of the Cellssupporting
confidence: 79%
“…Mitoxantrone, however, produced stronger increases in developed tension at lower stimulation frequencies in the present study, whereas a known inhibitor of the Na + -Ca 2+ exchange system, SEA0400, has been shown to produce a stronger increase in developed tension at higher stimulation frequencies in isolated ventricular muscle preparations obtained from mouse hearts [26]. These effects are expected because an inhibition of the Na + -Ca 2+ exchange system would elevate intracellular Ca 2+ concentrations more at higher stimulation frequencies when greater amounts of Ca 2+ enter the cells through the slow Ca 2+ channels [5,34].…”
Section: Discussioncontrasting
confidence: 79%
“…Sustained positive inotropy is observed in the rabbit, guinea pig, and rat ventricle, but in the guinea pig and rat, a transient decrease in contractile force is observed before the increase. The mouse ventricle shows a sustained negative inotropy in response to α-adrenoceptor stimulation (26) that is accompanied by decreased calcium transient amplitude (27). Electrophysiological and pharmacological analysis revealed that α-adrenoceptor stimulation activates the Na + /Ca 2+ exchanger and decreases the Ca 2+ released from the sarcoplasmic reticulum (28).…”
Section: Sympathetic Regulationmentioning
confidence: 99%